Machiavelli's Philosophical Anthropology. Issue 8 (16th November 2016) - Holman, Christopher
Abstract: This article seeks to address a tension in contemporary scholarship regarding Machiavelli's view of human nature. While it is common for readers to identify Machiavelli's rejection of any foundational law that determines the structure of the world, it is just as common for them to abstract human nature from this world and thereby to posit a fixed human essence. Machiavelli is thus seen as an anti-essentialist when it comes to external nature and as an essentialist when it comes to internal human nature. I will attempt to demonstrate, however, that for Machiavelli these two interpretations are integrated into an overall ontology of being that rejects all forms of essentialist thinking, including all positive models of human nature. Machiavelli's rejection of a fixed or positive human essence will be demonstrated by analyzing his account of the openness of human being to change and alteration by socialization, and his account of the multiplicity of forms of human doing and being. I argue that Machiavelli's rejection of a fixed essence underlies his affirmation of a negative essence—the specifically human desire for value-formation and the perpetual recreation of the world and, by extension, of the self. An appreciation of this affirmation, furthermore, has important consequences for how we think about Machiavelli's preferred form of republican institutionalization.